PATRIOTISM AND FIGHTING SPIRIT IN EPIC WORKS: ON THE EXAMPLE OF UZBEK WAR DASTANS - Bobur Elmurodov (Journals Park Publishing, 2024)
Mythology, history and literature, traditions and values of each nation are reflected in the core of folklore. Because the ancient tones, identity and character of the people's psyche develop through the examples of folk oral creativity. This article examines the scenes of patriotism, courage and fighting spirit reflected in the Uzbek war dastan “Yusuf and Akhmad” (“Yusuf bilan Ahmad”). This dastan was analyzed comparatively with battle scenes from other Turkic sources. Studying the bravery of heroes in these epics serves to increase the sense of patriotism and courage of military personnel.
Keywords: patriotism, fighting spirit, “Yusuf and Akhmad”, dualistic elements.